Nutrition Concerns of Insufficient and Excessive Intake of Dietary Minerals in Lactating Women: A Cross-Sectional Survey in Three Cities of China - Zhao, Ai (PLoS One, 2016)
OBJECTIVE: Objectives of this study were 1) to investigate the mineral intake by Chinese lactating women, 2) to explore the dietary source of minerals, and 3) the ratios between different dietary minerals. METHODS: A total of 468 lactating women in 5–240 days post-partum participated in this study. Food intakes by participants were measured using one time of 24-hour dietary recall, and minerals from food were calculated based on the Chinese Food Composition Table, second edition. RESULTS: In post-partum, women had inadequate food intake. 81.0% of women’s daily intake of dairy products was lower than 300g, and 97.1% of women’s daily intake of salt over 6g. For mineral intake, there were 81.8%, 59.0%, 47.6%, 45.7% and 66.8% of women’s calcium, magnesium, iron, zinc and selenium intake lower than the estimated average requirement, respectively, and 91.7% of women’s excessive intake of sodium. The calcium/phosphorus and sodium/potassium ratios were 0.41±0.26/1 and 3.13±2.89/1, respectively. Considering the dietary sources of minerals, 27.3%, 25.3% and 30.1% of iron, zinc and calcium were from animal-based food, respectively, and 60.3%, 66.1% and 58.0% of iron, zinc and calcium were from plant-based food, respectively. The phosphorus-protein ratio was 0.014±0.003/1. Lactation stage was associated with nutrient intake. Women within 30 days post-partum and the ones who live in Guangzhou had a significantly lower intake of certain minerals, while women with a high education experience had a high intake of calcium, potassium, iron and zinc. Productive age, whether obese or not, and delivery ways were not associated with mineral intakes (P all >0.05). CONCLUSION: Chinese women in three studied cities had an inappropriate food intake and resulted in both insufficient and excessive intakes of certain minerals.